Publication, Testing and Visualization with EFES: A tool for all stages of the EpiDoc XML editing process - BODARD, Gabriel; YORDANOVA, Polina (Studia Universitatis Babeș-Bolyai Digitalia, 2021)
EpiDoc is a set of recommendations, schema and other tools for the encoding of ancient texts, especially inscriptions and papyri, in TEI XML, that is now used by upwards of a hundred projects around the world, and large numbers of scholars seek training in EpiDoc encoding every year. The EpiDoc Front-End Services tool (EFES) was designed to fill the important need for a publication solution for researchers and editors who have produced EpiDoc encoded texts but do not have access to digital humanities support or a well-funded IT service to produce a publication for them.This paper will discuss the use of EFES not only for final publication, but as a tool in the editing and publication workflow, by editors of inscriptions, papyri and similar texts including those on coins and seals. The edition visualisations, indexes and search interface produced by EFES are able to serve as part of the validation, correction and research apparatus for the author of an epigraphic corpus, iteratively improving the editions long before final publication. As we will argue, this research process is a key component of epigraphic and papyrological editing practice, and studying these needs will help us to further enhance the effectiveness of EFES as a tool.To this end we also plan to add three major functionalities to the EFES toolbox: (1) date visualisation and filter—building on the existing “date slider,” and inspired by partner projects such as Pelagios and Godot; (2) geographic visualization features, again building on Pelagios code, allowing the display of locations within a corpus or from a specific set of search results in a map; (3) export of information and metadata from the corpus as Linked Open Data, following the recommendations of projects such as the Linked Places format, SNAP, Chronontology and Epigraphy.info, to enable the semantic sharing of data within and beyond the field of classical and historical editions.Finally, we will discuss the kinds of collaboration that will be required to bring about desired enhancements to the EFES toolset, especially in this age of research-focussed, short-term funding. Embedding essential infrastructure work of this kind in research applications for specific research and publication projects will almost certainly need to be part of the solution.